State selectivity in core ionization of methane - J. Rajput; J. Stindl; A. Cassimi; B. Gervais; M. Kircher; G. Kastirke; O. D. McGinnis; R. Enoki; J. B. Williams; V. Davis; R. Saha; S. Kumar; et al. (Physical Review Research)
A clear experimental signature of the population of the lowest triplet state ^{3}T_{1} of the methane dication is identified in a photoionization experiment. This state is populated only in valence ionization and is absent when the dication is formed by core ionization followed by Auger-Meitner decay. For valence ionization, the total internal energy of the CH_{3}^{+} fragment, formed during the deprotonation of CH_{4}^{2+}, is evaluated. Notably, the distribution of this internal energy peaks at the same value regardless of the initially populated electronic state of CH_{4}^{2+}. We find that excited electronic states of CH_{3}^{+} are predominantly populated with significant rovibrational excitation.